30 Year patterns of mortality in Tobago, West Indies, 1976-2005: impact of glucose intolerance and alcohol intake. - Mariam Molokhia (Public Library of Science (PLoS), 2011)
Objectives To determine the main predictors of all-cause and cardiovascular (CV) mortality in a rural West Indian population in Plymouth, Tobago over 30 years. Methods Questionnaire survey for CV risk factors and alcohol consumption patterns administered at baseline in 1976 with 92.5% response rate. 831/832 patients were followed up until 2005 or death. Results Hypertension (>140/90 mm Hg) was prevalent in 48% of men and 44% of women, and 21% of men and 17% of women had diabetes. Evidence showed most predictors for all cause and cardiovascular mortality having the main effects at ages <60 years, (p-value for interaction<0.01) but no risk factors having sex-specific effects on mortality. The main predictors of all-cause mortality at age <60 years in the fully adjusted model were high sessional alcohol intake (hazard ratio (HR) 2.04, 95% CI 1.10-3.80), severe hypertension >160/95 mm Hg (HR 1.68, 95% CI 1.09-2.60), diabetes (HR 3.28, 95% CI 1.89-5.69), and BMI (HR 1.04, 95% CI 1.00-1.07). The main predictors of cardiovascular mortality were similar in the fully adjusted model: high sessional alcohol intake (HR 2.47 95% CI 1.10-5.57), severe hypertension (HR 2.78 95% CI 1.56-4.95), diabetes (HR 3.68 95% CI 1.77-7.67) and additionally LVH, (HR 5.54 95% CI 1.38-22.26), however BMI did not show independent effects. For men, high sessional alcohol intake explains 27% of all cause mortality, and 40% of cardiovascular mortality at age <60 yrs. In adults aged <60 years, the attributable risk fraction for IGT/Diabetes and all cause mortality and cardiovascular mortality is 28% in women vs. 11% in men, and 22% in women vs. 6% in men respectively. Conclusions In this Afro-Caribbean population we found that a major proportion of deaths are attributable to high sessional alcohol intake (in males), diabetes, and hypertension and these risk factors primarily operate in those below 60 years.